Hubungan Konsumsi Protein dan Vitamin C dengan Status Kebugaran pada Mahasiswa Program Studi Gizi Fakultas Ilmu Kesehatan UPN Veteran Jakarta - Iin Fatmawati; Yehuda Kristiyanto Putra; Widayani Wahyuningtyas (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2021)
Physical fitness is related to risk factors of various illness and death in current times. Fitness status is generally affected by two factors, internal and external factors. One of the external factors that affects fitness status is nutrient intake. Protein and vitamin C are nutrients that influence physical fitness status. This study aimed to observe the relationship between protein and vitamin C intake with physical fitness status among students of Nutrition Study Program in Health Sciences Faculty, Universitas Pembangunan Nasional Veteran Jakarta. This is a cross-sectional study with a total of 80 students recruited randomly (stratified random sampling). Bivariate analysis showed a significant relationship between protein intake with physical fitness status (p=0.017). Similarly, vitamin C intake is significantly correlated with physical fitness status (p=0.009). Therefore, it can be concluded that protein and vitamin C intake are significantly correlated with physical fitness status among Nutrition Program Study students in Health Sciences Faculty in Universitas Pembangunan Nasional Veteran Jakarta. Protein and vitamin C intake that is not in accordance with daily need may cause poor physical fitness status.